An investigation of plant-induced suction and its implications for slope stability. Issue 2 (30th April 2019) - Yildiz, Anil; Graf, Frank; Springman, Sarah M.
Abstract : Both above- and below-ground biomass of plants provide additional strength to soil through different mechanisms, which help to increase the stability of a vegetated slope. Nonetheless, shallow landslides on steep slopes covered with vegetation still occur, often being triggered above the groundwater table, due to loss of suction subsequent to rainfall. Therefore, it is essential to know to what extent vegetation enhances slope stability, and to quantify the contribution of vegetation to the shear strength of soil to determine factors of safety. Results of large-scale direct shear experiments on root-permeated soils and slope geometry from a landslide database were synthesised through an infinite slope analysis under partially saturated conditions to find critical combinations of slope angle and suction stress. Monte Carlo simulations yielded a clear separation of stable and unstable zones, which can be used to define the susceptibility of a slope to near surface failure. This method, based on the simulations, has the potential to be used as a regional early warning system.